2014
DOI: 10.11118/actaun200856040231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed, sex and litter size on growth and meatiness and fattiness in vivo in lambs

Abstract: The main aim of the study was the evaluation of the effects of breed (Suffolk, Merinoladschaf, Oxford Down and Charollais), sex and litter size (singles, twins and triplets) on growth. The study was carried out on the farm in Žabčice in 2007. Within the frame of evaluation of meatiness and fattiness in vivo in lambs the following ultrasound measurements were carried out: depth of musculus longissimus lumborum et thoracis (Dm.l.l.t.) and fat thickness (FT). Ultrasound measurements was done between last pectoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The male lambs deposit more of their muscle mass in the chest area than in the dorsal area where ultrasonography is performed (Milerski et al, 2006). The effect of lamb sex is also reported by Burfening and Carpio (1993);El Fadili et al (2000); Peña et al (2005); Kuchtík and Dobeš (2006); Hošek et al (2008); Rashidi et al (2008); Štolc et al (2011) and Rahimi et al (2014). Ewes 1-2 years old had in our study significant negative effect on the meat performance of lambs.…”
Section: Growth Analysissupporting
confidence: 87%
“…The male lambs deposit more of their muscle mass in the chest area than in the dorsal area where ultrasonography is performed (Milerski et al, 2006). The effect of lamb sex is also reported by Burfening and Carpio (1993);El Fadili et al (2000); Peña et al (2005); Kuchtík and Dobeš (2006); Hošek et al (2008); Rashidi et al (2008); Štolc et al (2011) and Rahimi et al (2014). Ewes 1-2 years old had in our study significant negative effect on the meat performance of lambs.…”
Section: Growth Analysissupporting
confidence: 87%
“…In addition, FLs of the present study had also the lower BW0 compared to MLs which is consistent with the finding of Taskin et al (2012). In contrast, Hošek et al (2008) found the higher BW0 in FLs. It is interesting, that EL in FLs of the present study, compared to MLs, was positively correlated (P < 0.05) with DGs from birth to 100 days of age and from birth to the slaughter.…”
Section: Resultsmentioning
confidence: 67%
“…The evaluation of BCS was carried out by the same person according to Russel et al (1969), on a 1-5 scale (BCS 1 = emaciaded, BCS 5 = obese). The ultrasound measurements (UMs) of DMLLT and TBF were carried out by the same person according to Hošek et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Growth intensity of lambs before weaning and after weaning significantly affects the economics of farming (Petr et al, 2009;Pajor et al, 2008;2009a;Wolfová et al, 2009;Komprda et al, 2012;Svitáková et al, 2014;Koutná et al, 2016). The growth is affected by many factors where the most important are the breed, nutrition, sex, litter size, management, biotic stress, health and age of mothers (Kuchtík and Horák, 2007;Dobeš et al, 2007;Hošek et al, 2008;Pajor et al, 2007;2009b;Kuchtík et al, 2010;Zapletal et al, 2010;Štolc et al, 2011;Ptáček et al, 2013;Lupi et al, 2015;Waheed et al, 2015;Aguirre Riofrio et al, 2016;Mellado et al, 2016;Moreira et al, 2016;Sieklicki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%